Neurochemical Changes in the Brain After Fetal Exposure to Fluoxetine, A Serotonin Reuptake Inhibitor (SRI) in Rodents - Alonazi, Mona A.; El Gezeery, Amina; El-Ansary, Afaf; Bhat, Ramesa Shafi (Current Proteomics, 2021)
Background: In utero exposure to Selective Serotonin Reuptake Inhibitors (SSRI) is considered a risk factor for many neurodevelopmental diseases. Objective: The aim of this study was to investigate whether prenatal SSRI exposure changes newborn brain chemistry. Methods: An animal-based study was designed in which the utero SSRI exposed rat pups were compared to one without drug exposure. Neurochemical changes in the infants were assessed after 2 days of birth by estimating the levels of inflammatory cytokines, neurotransmitters, and caspases in the brain exposed to SSRI at the prenatal stage and compared to normal unexposed newborns. Results: Our results showed significant neurochemical changes in SSRI-exposed newborns. A significant decrease in dopamine, and serotonin levels with a remarkable decrease in noradrenaline in addition to remarkable increase of IFN-γ and caspase-3 levels was observed in the brain tissues of prenatal exposed SSRIs rat pups. Conclusion: The results suggest that prenatal SSRI treatment may affect brain development of newborn hence should be done warily during the gestation period.
Keywords: Depression